Analisis Rasio Solvabilitas Dan Profitabilitas Untuk Mengukur Kinerja Keuangan Pada PT. Jamu dan Farmasi Sido Muncul, Tbk Periode 2017-2023: Analysis of Solvency and Profitability Ratios to Measure Financial Performance at PT. Jamu and Farmasi Sido Muncul, Tbk Period 2017-2023 - Nursin, Depianti; Halimu, Mastia M; Ali, Rendi Pranata (Jurnal Ilmiah Produktif, 2025)
This study aims to determine the financial performance of PT. Jamu and Farmasi Sido Muncul, Tbk using solvency and profitability ratios. This study was analyzed using descriptive analysis techniques, namely data in the form of figures including financial reports in the form of balance sheets and profit and loss data reports at PT. Jamu and Farmasi Sido Muncul, Tbk in 2017-2023 which describe the conditions or events in a real company. The variables used are the solvency ratio projected with the debt to asset ratio and debt to equity ratio and the Profitability Ratio projected with Net profit margin and Return on assets. The results of the study indicate that the Debt to Total Asset Ratio and Debt to Equity Ratio can be said to be less than good. This is evidenced by the results of the calculation of the two solvency ratios, most of which have increased from year to year. Financial performance is measured by the profitability ratio projected with the net profit margin can be said to be good. However, calculated based on the return on asset ratio, most of the financial performance is less than good. Shows that the company has a large financial risk, but also has a great opportunity to generate high profits. From the results obtained, this is due to the company being less able to optimize the resources owned by the company. Both from resources in the form of capital, assets and investments that do not produce enough profit or profit in terms of utilization, the increase fluctuates every year.